2022
DOI: 10.1021/acsaem.1c04115
|View full text |Cite
|
Sign up to set email alerts
|

New Pb-Free Stable Sn–Ge Solid Solution Halide Perovskites Fabricated by Spray Deposition

Abstract: Considering the toxicity of lead ions, substituting Pb with nontoxic elements in halide perovskites, HaPs, has become one of the most significant challenges associated with these materials. Here, we report on replacing Pb with Sn and Ge, focusing on an all-inorganic HaP, CsSn x Ge1–x Br3, and using a multihead spray deposition setup for thin-film formation to overcome the low solubility of the precursors and improve film coverage. We find that, in this way, we can form CsSn x Ge1–x Br3 films up to high x value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…The presence of GeI 2 in the perovskite crystals would cause oxidation from GeI 2 to GeO 2 , which is a more stable passivation layer formed at the perovskite crystal surface rather than fragile PbO. 30,36–38 With the presence of all these tetra- n -alkyl ammonium cations used in this study, full dissociation of GeI 2 in these perovskite precursors was successfully obtained due to the coordination between Ge 2+ and the quaternary amines. Unfortunately, the low solubility of TEAI (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The presence of GeI 2 in the perovskite crystals would cause oxidation from GeI 2 to GeO 2 , which is a more stable passivation layer formed at the perovskite crystal surface rather than fragile PbO. 30,36–38 With the presence of all these tetra- n -alkyl ammonium cations used in this study, full dissociation of GeI 2 in these perovskite precursors was successfully obtained due to the coordination between Ge 2+ and the quaternary amines. Unfortunately, the low solubility of TEAI (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…[ 68 ] Adi kama et al in their investigation showed power output of 0.25 μW cm −2 for their CsGeI3 device. [ 69 ] Another report showed an experimental efficiency of 3.2% for CsGeI 3 . [ 15 ] Thermal evaporation‐deposited thin film of CsGeI 3 perovskite with high crystallinity, uniformity, and good response in the visible region is demonstrated by Zeng et al [ 70 ] Efficiency as high as 7% is shown for the Sn–Ge mixed CsSn 0.5 Ge 0.5 I 3 device with significant stability.…”
Section: Stability Aspect Of Ge‐based Inorganic Perovskitesmentioning
confidence: 99%
“…According to literature reports, solvothermal‐grown CsGeI 3 , a purely Ge‐based absorber, has shown an efficiency of 4.94% and reported similar stability as MAPbI3. [ 34 ] Other studies have shown lower efficiencies, with Krishnamoorthy et al demonstrating an efficiency of 0.11% for CsGeI 3 , [ 35 ] Adi Kama et al reported a power output of 0.25 μW cm −2 for their CsGeI3 device, [ 36 ] and another report showed an experimental efficiency of 3.2% for CsGeI 3 . [ 37 ] Zeng et al demonstrated the deposition of thermal evaporation thin films of CsGeI 3 perovskite with high crystallinity, uniformity, and good response in the visible region.…”
Section: Stability Aspect Of Ge‐based Perovskite Solar Cellsmentioning
confidence: 99%